Color Doppler ultrasonography in ocular Behcet's disease - Çelebi, S; Akfirat, M; Çelebi, H; Alagöz, G (Scriptor Publisher, 2000)
Purpose: The aim of this prospective study was to assess the ocular hemodynamic changes in patients with Behcet's disease who had involvement of the posterior segment by color Doppler ultrasonography, Methods: The present study was carried out in 32 eyes of 24 patients with ocular Behcet's disease and 42 eyes of 21 persons as a healthy age-matched control group. In order to detect the hemodynamic changes in ocular Behcet's disease, peak systolic and end-diastolic velocities (PSV, EDV; cm/sec), resistive and pulsatile indices (RI, PT), and PSV/EDV ratio of central retinal artery (CRA), short posterior ciliary artery (PCA) and ophthalmic artery (OA) were determined. Results: The mean PSV and EDV (8.1+/-2.6 and 2.7+/-0.1 cm/sec, respectively) in the CRA were significantly lower in patients with Behcet's disease than in healthy controls (11.5+/-2.2 and 3.5+/-1.0 cm/sec, respectively, p<0.001), For the PCA, these values (12.7+/-4.2 and 4.3+/-1.1 cm/sec, respectively) were significantly lower in the patient group than in the control the group (18.2+/-4.2 and 6.1+/-2.5 cm/sec, respectively, p<0.001), In the patient group, a statistically significant decrease compared to the control group was detected in the mean PSV of the OA (31.8+/-8.2 and 35.8+/-0.6 cm/sec, respectively, p<0.02), However, no significant difference in the other parameters of these vessels was observed between groups. Conclusions: These results demonstrate the presence of some circulatory changes in the flow velocities of the CRA, PCA and OA in patients with Behcet's disease when compared with control subjects.
Keywords: Behcet's disease; color Doppler ultrasonography; central retinal artery; short posterior ciliary artery; ophthalmic artery